PENERAPAN HUKUM WARIS ISLAM DALAM PRAKTIK KEHIDUPAN MASYARAKAT LOLOAN TIMUR JEMBRANA BALI - Mulya Akmal; Ahmad Saikhuddin; Doni Amirul (Institut Teknologi Bisnis dan Kesehatan Bhakti Putra Bangsa Indonesia, 2023)
In general, inheritance law in Bali applies the principle or system of patrilineal kinship where a man has full rights in becoming an heir, while a woman has the right to enjoy the proceeds or property of the man, through her status as a wife or a child. Women in the view of Balinese customary inheritance law still have the opportunity to become heirs but must go through certain conditions that must be met. This study aims to explore further the application of Islamic inheritance law in East Loloan, Jembrana, Bali. This study uses an empirical approach. The research technique uses observational interviews and documentation. Data analysis using triangulation. The results showed that 96% of the population in East Loloan is Muslim. For this reason, the implementation of inheritance law in East Loloan uses Islamic law, also guided by the Compilation of Islamic Law (KHI). As long as there is an opportunity to be resolved by Islamic law, then the application of inheritance law uses Shari'a. In other words, Balinese customary inheritance law cannot be applied in East Loloan, considering that there is a concept of peace or takharuj in accordance with Article 174 of the KHI.